2019
DOI: 10.4103/jpgm.jpgm_489_18
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and satisfaction in faculty of a teaching hospital in south India

Abstract: Background:There are multiple economic, psychological, and physical consequences of high job stress, low job satisfaction and burnout in faculty of a teaching hospital in South India. Data from developing countries on these domains are sparse.Materials and Methods:In a cross-sectional study we assessed the prevalence and sources of perceived job stress, job satisfaction and burnout in faculty, as well as ways of coping with stress among consenting faculty of a large, private, charitable, teaching hospital in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
(39 reference statements)
1
15
1
3
Order By: Relevance
“…A study on faculty doctors from the southern part of India revealed high perceived job stress among doctors aged <45 years (73%) compared to 18% of those aged >45 years. 24 Our study revealed that doctors in clinical specialties had fewer anxiety symptoms than those in non-clinical specialties. Marital status and the current working department had no significant impact on the prevalence of anxiety symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…A study on faculty doctors from the southern part of India revealed high perceived job stress among doctors aged <45 years (73%) compared to 18% of those aged >45 years. 24 Our study revealed that doctors in clinical specialties had fewer anxiety symptoms than those in non-clinical specialties. Marital status and the current working department had no significant impact on the prevalence of anxiety symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…Burnout in medical practitioners, residents, and faculty population has been addressed in Indian studies;[ 16 17 18 19 20 21 ] however, to the authors' knowledge, only a few studies have reported on medical students' burnout. [ 22 23 24 ] None of the studies have estimated the prevalence of burnout or reported on the influence of resilience on burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Chichra et al [2] have conducted a large sample study covering about 42 clinical and non-clinical departments, but non-response rate was also high. More than one third of the faculty had not responded to the questionnaire, and probably the reasons for that could have been explored so as to understand if those who declined were under more stress or had any other reasons.…”
mentioning
confidence: 99%
“…The concerned study[2] has addressed a very valid and ongoing concern among medical professionals. Chichra et al [2] have identified an inverse relationship of stress with job satisfaction and high level of burnout among the consultants.…”
mentioning
confidence: 99%
See 1 more Smart Citation